Defining and validating a Body Skin Discomfort Index (BSDI). (4th October 2018) - Segot‐Chicq, E.; Salah, S.; Jullien, M.; Portal, N.; Deschodt, C.; Gagnebien, D.
Abstract: Objective: To understand the drivers of body skin discomfort and to validate a new index to assess its severity. This index should be sensitive enough to capture changes in response to treatment. Methods: Previous consumer studies suggested seven potential main dimensions behind skin discomfort. Four of them refer to self‐declarations (stinging, itching, warming and tightening), whereas three can be assessed by a dermatologist (skin dryness, redness and desquamation). Intensity and frequency or extent of these items were measured using 0–9 ordinal scales. To generate the data for validation of a new index based on the 7 items, a group of 49 subjects complaining of skin discomfort was followed up for 5 weeks: 1‐week without product application to check reproducibility, followed by 4 weeks of treatment to evaluate sensitivity to change. Items not significantly reported at baseline or with changes because of treatment not sufficiently correlated with the overall change measured by the index were discarded. A control group of 49 subjects presenting no discomfort at all was also included to check the capacity of our index to discriminate both groups. The final index (Body Skin Discomfort Index, BSDI) was normalized to facilitate the clinical interpretation of the results. Results: After discarding warming and skin redness, the BSDI is finally a five‐dimension score calculated as follows: (TI + TF + SI + SF + ItI + ItF + DI + DE + DqI + DqE) 9 9/90 where T, S, It, D and Dq refer to tightness, stinging, itching, dryness, desquamation respectively, and I, F or E refers to intensity, frequency or extent. The final BSDI score displayed a good capacity to discriminate people with skin discomfort from people with 'normal skin', a good reproducibility (intraclass coefficient correlation ICC = 0.85) and a good sensitivity to detect change because of treatment (Difference vs. Baseline of 2.63 on a 0–9 scale). Conclusion: The developed index, BSDI, is a reliable way to address the measurement issue of the multidimensional skin discomfort syndrome. It thus should simplify the evaluation of cosmetic products effect and helps to compare products dedicated to body cleansing.